Fetuin-A Thr256Ser gene polymorphism as a mortality predictor in patients with chronic kidney disease on maintenance haemodialysis in Medan, Indonesia - Riri Andri Muzasti; Dr Suhardjono; Bambang Purwanto; Rosita Juwita Sembiring (Medicinski glasnik, 2019)
Aim: To investigate an impact of Fetuin-A Thr256Ser gene polymorphism on the mortality rate of chronic kidney disease on maintenance haemodialysis patients in Indonesia. Methods: This is an analytic-longitudinal observational study using survival analysis with nine-month follow up on 106 maintenance haemodialysis patients. The PCR-RFLP is used to determine Fetuin-A Thr256Ser gene polymorphism and Fetuin-A serum level measured by using ELISA methods. We use time-independent cox regression analysis to investigate factors that contribute to patient survival. Results: The mean survival time of this study is 8.49±1.53 months, with a median survival of 9 months (range 1-9 months). Among 12 (11.3%) deceased patients, most of them carried GG genotype with 8.87 times risk of mortality compared to those with CC+CG genotype (p=0.005). The group of patients with IL-6 level ?86.9 pg/mL had higher mortality with 3.64 times greater risk compared to those with IL-6 level, <86.9 pg/mL (p=0.03). Conclusion: This study revealed a significant dominance independent impact of the Fetuin-A Thr256Ser gene polymorphism on the survival rate of maintenance haemodialysis patients. These results suggest that genotype variation of Fetuin-A gene could be a potential marker to identify high mortality risk in Indonesia's maintenance haemodialysis patients, especially in Medan.
Keywords: alpha-2-HS-glycoprotein; haemodialysis; mortality